SISTEM INFORMASI ADMINISTRASI PEMBAYARAN SPP BERBASIS WEB PADA PONDOK PESANTREN PAKKUSIANTA AL-ISTIQAMAH - Sa’adah, Siti; Candra, Adi; Iryani, Juniarti (CV. LAJAGOE PUSTAKA, 2025)
This study aims to: (1) Know the form of a valid web-based SPP payment administration information system design at the Pakkusianta Al-Istiqamah Bulukumba Islamic boarding school. (2) To find out the user's response to the web-based SPP payment administration information system at the Pakkusianta Al-Istiqamah Bulukumba Islamic boarding school. This research uses 4D methods, namely Define, Design, Development, and Disseminate. The test method used is Black box testing. The results of this study are (1) Web-based SPP payment administration information system at Pesantren Pakkusianta Al-Istiqamah Bulukumba which can present data more efficiently and can store processed results. The web-based SPP payment administration information system is built using PHP programming language and MySql database. System design uses UML (Unifield Modeling Language) language which consists of use case diagrams, sequence diagrams, activity diagrams, and class diagrams. (2) The calculation result of the respondent's assessment is obtained a percentage of 92.4%. This percentage falls into the very good category.